Gender Equality in Politics (Study on The Indonesian Constitutional Court's Decisions on Judicial Review Related to Women's Political Participation) - Riris Ardhanariswari; Tenang Haryanto; Supriyanto Supriyanto (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Such conception of human rights is in line with international human rights law, in particular with adopting a comprehensive women's rights instrument, namely the Convention on the Elimination of All Forms Discrimination Against Women, hereinafter referred to as the CEDAW Convention, which was ratified by the State of Indonesia with Law No. 7 of 1984 on Ratification of the CEDAW Convention. Women, especially in Indonesia are still left behind both in public life and politics. This raises the issue of gender equality, which means a condition of